Postmortem conception in selected common law countries - Marszelewski, Michał (Studia Iuridica Toruniensia, 2015)
This article covers issues concerning legal regulations related to the postmortem conception in Australia, Canada, New Zealand and the United States of America. To achieve this, a detailed analysis of current legislation and selection of the important judicial decisions which in common law countries have law – making character was carried out. The paper also includes a number of facts describing particular circumstances of conception of the child after the death of his genetic parent and significant to this fact opinions, often formulated by the judges. Moreover, the article contains numerous acts, recommendations and guidelines which are not legally binding, but have an important voice in the debate over the analyzed issue. Due to the fact that, in some cases, postmortem regulations are in statu nascendi, the paper indicates possible directions of future law development in presented area